دور معلومات محاسبة الاستدامة في تعزيز الأداء المنظمي دراسة استطلاعية تحليلية لشركتي - سعيد, به يمان عثمان (Sulaimani Journal for Humanities, 2021)
This research aims to study the role of sustainability accounting on improving organizational efficiency. From the sense that using any piece of information regarding performance must be processed, regardless the information is social, environmental or financial information. The processing involves gauges and indicators of sustainability accounting and terminologies that are repeated mostly in academic conferences and in performances either inside or outside the organizations. This raises the impact of sustainability accounting information on organizational efficiency improvement on the one hand, and what can be understood through sustainability accounting on the other hand. Therefore, this research collected numerous aims in which the most significant aim is the diagnosis of sustainability accounting information. Highlighting the level of organizational performance in Al Hadid Company is another key aim of this study. Further, this research is significant since similar studies in Arabic are very rare. The research assumes that there is no significant effect of sustainability accounting information on organizational performance improvement. This research employed SPSS program for analytical purposes. Accordingly, several findings outlined at the end of the research. The main conclusion was that sustainability accounting is capable of preparing industrial organization behaviors for minimizing the expenditures of reducing pollution, encouraging recycling and installing equipment for cleaning the environment. In addition to a number of recommendations, most importantly Al-Hadid company should adopt sustainability accounting through the adoption of social responsibility because it has an important role in enhancing organizational performance.
Keywords: sustainability accounting; performance; indicators and measurement